2014
DOI: 10.1039/c3ra45083j
|View full text |Cite
|
Sign up to set email alerts
|

Efficient one-pot synthesis of highly monodisperse carbon quantum dots

Abstract: Type of publicationArticle (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…We have recently demonstrated that similar sized CQDs exhibit distinctly different absorbance and photoluminescence spectra when capped with ligands of different polarity, underlining the importance of the surface in determining their photophysical properties. 7,26 Due to the high degree of monodispersity within those samples, we concluded the most plausible explanation was that the excitation wavelength dependence observed originated from recombination of photogenerated excitons at different surface trap states. Since the surface of the CQDs were capped using the same ligand functionalisation method, any variation in the PL spectra shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently demonstrated that similar sized CQDs exhibit distinctly different absorbance and photoluminescence spectra when capped with ligands of different polarity, underlining the importance of the surface in determining their photophysical properties. 7,26 Due to the high degree of monodispersity within those samples, we concluded the most plausible explanation was that the excitation wavelength dependence observed originated from recombination of photogenerated excitons at different surface trap states. Since the surface of the CQDs were capped using the same ligand functionalisation method, any variation in the PL spectra shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…25 The size of the CQDs was controlled by regulating the amount of the emulsifier. Previously, we reported the synthesis of size monodisperse CQDs using a room temperature microemulsion strategy, 7,26 see Fig. 1.…”
mentioning
confidence: 99%
“…One widespread problem in CDs nanoscience is the heterogeneity of most CD samples, in the sense that several synthesis routes tend to yield CDs with a large degree of structural heterogeneity, such as very broad size distributions, large dot-to-dot variations in surface structure, optical heterogeneity, or the contamination of the sample by small fluorescent molecules produced together with CDs. Therefore, aside a few exceptions [84], the use of a purification method is often crucial to achieve a full control on the size dispersion of the synthesized nanosystems, or select some sub-sets of CDs based on their size or their surface structure. In some cases, separation methods have been used simply to select the most fluorescent part of a CD sample, out of a heterogeneous distribution of fluorescent quantum yields [10,85], leading to some of the highest fluorescence quantum yields reported in the literature.…”
Section: Purification and Separation Methodsmentioning
confidence: 99%
“…For example, Kwon and Rhee used reverse micelles as nanoreactors to synthesize luminescent nanoparticles under the reaction temperature of 160 °C . Linehan and Doyle fabricated fluorescent nanoparticles through the metal reduction of carbon precursors in reverse micellar nanoreactors . However, most micellar nanoreactor approaches for PCPNs preparation require high temperature and involve the addition of toxic organic solvents or metal catalysts and the use of more than one chemical.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Linehan and Doyle fabricated fluorescent nanoparticles through the metal reduction of carbon precursors in reverse micellar nanoreactors. [20] However, most micellar nanoreactor approaches for PCPNs preparation require high temperature and involve the addition of toxic organic solvents or metal catalysts and the use of more than one chemical. Therefore, the fabrication of PCPNs using vesicles as nanoreactors under ambient temperature and without a catalyst is crucial for scientific research and industry.…”
Section: Introductionmentioning
confidence: 99%